PENGARUH HARGA DAGING SAPI DOMESTIK, HARGA DAGING SAPI LUAR NEGERI DAN NILAI KURS TERHADAP IMPOR DAGING SAPI INDONESIA - Agnes vanessa; Yurina Yurina (LPPM Universitas Malikussaleh - Indonesia, 2022)
This study aims to influence domestic beef prices, foreign beef prices and exchange rates on Indonesian beef imports. The data used in this study is secondary data from 1996-2020 obtained from the World Bank, the Central Statistics Agency and the Indonesian Ministry of Agriculture. The data analysis method used is Multiple Linear Regression Analysis using Eviews Software. The results obtained in this study prove that partially the Domestic Beef Price has a significant effect on Beef Imports in Indonesia and partially the Foreign Beef Price and Exchange Rate have no significant effect on Beef Imports in Indonesia and simultaneously the Domestic Beef Price, Overseas Beef Price and Exchange Rate have a significant effect on Beef Imports in Indonesia. The suggestion in this study is that it is hoped that the government will pay more attention to the Beef Import Sector in Indonesia